International Marketing Strategy of Transformations LTD in Sierra Leone - Alam, Mohammed Touqeer (2011)
The central idea of the report is to formulate an international marketing strategy for Transformations Ltd, a learning and development company based in UK for its entry in Sierra Leone market. The company wants to provide accredited British Leadership and Management qualification in Sierra Leone.